Feasibility of Using HIV Care-Continuum Outcomes to Identify Geographic Areas for Targeted HIV Testing. (1st February 2017) - Castel, Amanda D.; Kuo, Irene; Mikre, Meriam; Young, Toni; Haddix, Meredith; Das, Suparna; Maugham, Geoffrey; Reisen, Carol
Abstract : Background: Improved detection and linkage to care of previously undiagnosed HIV infections require innovative approaches to testing. We sought to determine the feasibility of targeted HIV testing in geographic areas, defined by continuum of care parameters, to identify HIV-infected persons needing linkage or engagement in care. Methods: Using HIV surveillance data from Washington, DC, we identified census tracts that had an HIV prevalence >1% and were either above (higher risk areas—HRAs) or below (lower risk areas—LRAs) the median for 3 indicators: monitored viral load, proportion of persons out of care (OOC), and never in care. Community-based HIV rapid testing and participant surveys were conducted in the 20 census tracts meeting the criteria. Areas were mapped using ArcGIS, and descriptive and univariate analyses were conducted comparing the areas and participants. Results: Among 1471 persons tested, 28 (1.9%) tested HIV positive; 2.1% in HRAs vs. 1.7% in LRAs ( P = 0.57). Higher proportions of men (63.7% vs. 56.7%, P = 0.007) and fewer blacks (91.0% vs. 94.6%, P = 0.008) were tested in LRAs vs. HRAs; no differences were observed in risk behaviors between the areas. Among HIV-positive participants, 54% were new diagnoses (n = 9) or OOC (n = 6), all were Black, 64% were men with a median age of 51 years. Conclusions: Although significant differences in HIV seropositivity were not observed between testing areas, our approach proved feasible and enabled identification of new diagnoses and OOC HIV–infected persons. This testing paradigm could be adapted in other locales to identify areas for targeted HIV testing and other reengagement efforts.